Phase transition and magnetocaloric properties of Mn50Ni42-xCoxSn8 (0 < x < 10) melt-spun ribbons - Li, Zongbin (2018)
The characteristics of magnetostructural coupling play a crucial role in the magnetic field-driven behaviour of magnetofunctional alloys. The availability of magnetostructural coupling over a broad temperature range is of great significance for scientific and technological purposes. This work demonstrates that strong magnetostrucural coupling can be achieved over a wide temperature range (222 to 355 K) in Co-doped high Mn-content Mn50Ni42−xCoxSn8 (0 ≤ x ≤ 10) melt-spun ribbons. It is shown that, over a wide composition range with Co content from 3 to 9 at.%, the paramagnetic austenite first transforms into ferromagnetic austenite at T C on cooling, then the ferromagnetic austenite further transforms into a weakly magnetic martensite at T M. Such strong magnetostructural coupling enables the ribbons to exhibit field-induced inverse martensitic transformation behaviour and a large magnetocaloric effect. Under a field change of 5 T, a maximum magnetic entropy change ΔS M of 18.6 J kg−1 K−1 and an effective refrigerant capacity RC eff of up to 178 J kg−1 can be achieved, which are comparable with or even superior to those of Ni-rich Ni–Mn-based polycrystalline bulk alloys. The combination of high performance and low cost makes Mn–Ni–Co–Sn ribbons of great interest as potential candidates for magnetic refrigeration.